Desain Kurikulum Pendidikan Islam Inklusif untuk Meningkatkan Akses dan Keadilan Pendidikan di SMP Muhammadiyah Pinrang - Abdul Rahman (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study is motivated by persistent disparities in access to Islamic education influenced by economic, geographical, and socio-cultural factors, particularly at SMP Muhammadiyah Pinrang. These conditions indicate that the existing curriculum has not fully reflected principles of equity and justice, thus requiring an inclusive curriculum design. This study aims to analyze the concept of an inclusive Islamic education curriculum, identify the principles of its design, and formulate curriculum development strategies that can improve access and educational equity. This research uses a qualitative approach with a literature study method. Data were obtained from primary and secondary sources, including books, scientific journals, and policy documents, which were analyzed using content analysis techniques. Research results show that an inclusive Islamic education curriculum must be based on the principles of accessibility, equality, learning flexibility, and recognition of student diversity. The developed curriculum model emphasizes the integration of Islamic values with a student-centered learning approach and differentiated instruction. The implementation of this curriculum requires teacher competency support, integration of educational technology, as well as supportive policies. The application of an inclusive curriculum has been proven to increase participation, motivation, and fairness in education, as well as promote the creation of an Islamic education system that is more adaptive and relevant to the demands of the times.